AN ANALYSIS OF ENGLISH WORKSHEET ENTITLED “MAESTRO” USED TO TEACH ELEMENTARY SCHOOL STUDENTS GRADE FIVE - Kadek Yati Fitria Dewi (Daiwi Widya, 2014)
Teaching and learning components is related to the use of textbook and student worksheet as learning media. There are a number of drawbacks shown in the textbook and student worksheet that are currently used in schools. The drawbacks include the content validity and face validity. Thus, this study aimed at analyzing drawbacks found in the English student worksheet entitled “Maestro” used to teach elementary students grade five. This study employed documentary analysis method of data collection. After being collected, the data were reduced to the main focused of the study. And then, they were analyzed and displayed. From the study, it was found that the drawbacks found in the English student worksheet entitled “Maestro” were dealing with face validity and content validity. Due to the face validity, there were many errors presented. The errors made were mostly about the overuse or the inappropriate use of auxiliary verb, spelling, and punctuation related to the use of clause. Moreover, the materials were also presented using plain paper and color. Due to the content validity, it was found that the materials did not help learners to feel at ease; they did not take into account that learners are differ in learning styles; and they did not provide learners with opportunities to use the target language to achieve communicative purposes.